2009
DOI: 10.1128/mcb.00336-08
|View full text |Cite
|
Sign up to set email alerts
|

The Transforming Rho Family GTPase Wrch-1 Disrupts Epithelial Cell Tight Junctions and Epithelial Morphogenesis

Abstract: Wrch-1, an atypical and transforming Rho GTPase, regulates cellular activities including proliferation and actin organization, but its functions and effectors remain poorly characterized. We show here that Wrch-1 distributes along the apical and basolateral membranes in MDCK cells and binds the cell polarity protein Par6 in a GTP-dependent manner. Activated Wrch-1 negatively regulates the kinetics of tight junction (TJ) assembly during epithelial cell polarization but has no detectable effect on overall cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 50 publications
3
65
0
Order By: Relevance
“…Consistent with the cell culture results, in Xenopus embryos, in which Rhou is expressed in migrating cranial neural crest cells, Rhou knockdown impairs cell migration (Fort et al, 2011). In MDCK (canine kidney epithelial) cells, overexpression of Rhou disrupts tight junction formation and the distribution of F-actin, and depletion of Rhou disrupts lumen formation in cysts (Brady et al, 2009). The findings of these studies suggest that Rhou plays a role in regulating epithelial cell shape and structure and modulating cellular behaviour.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Consistent with the cell culture results, in Xenopus embryos, in which Rhou is expressed in migrating cranial neural crest cells, Rhou knockdown impairs cell migration (Fort et al, 2011). In MDCK (canine kidney epithelial) cells, overexpression of Rhou disrupts tight junction formation and the distribution of F-actin, and depletion of Rhou disrupts lumen formation in cysts (Brady et al, 2009). The findings of these studies suggest that Rhou plays a role in regulating epithelial cell shape and structure and modulating cellular behaviour.…”
Section: Introductionsupporting
confidence: 61%
“…Reduced Rhou activity affects cellular morphology and cytoskeletal organization in cultured cells Brady et al, 2009;Saras et al, 2004). Of particular note, Rhou knockdown in MDCK cells disrupts epithelial cyst formation in a three-dimensional matrix (Brady et al, 2009). These findings suggest that Rhou activity is essential for the maintenance of cellular and tissue architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of endothelial cells lacking CCM1 or CCM2 (10,13,21) have demonstrated an increased formation of actin stress fibers and an increase in the activity of Rho, a small GTPase known to negatively regulate both endothelial and epithelial cell junctions (26)(27)(28)(29). We therefore next measured the effect of loss of CCM3 and the STKs on stress fiber formation and Rho activity.…”
Section: Ccm3 and Stks Regulate Endothelial Cell Junctions Genetic Smentioning
confidence: 99%
“…By contrast, RhoV does not contain PRMs in its N-terminal extension. The sequences in RhoU are PAFPDR (residues 8-13), PPVPPRR (20)(21)(22)(23)(24)(25)(26) and PGEPGGR (36-42) (Figure 4). The N-terminal region of RhoU binds to various SH3-domain containing adaptor proteins, including Grb2, 5,14 Nck2 5,6 and phospholipase Cg.…”
mentioning
confidence: 99%